INNOVATIVENESS AND SALES PERFORMANCE OF SMALL AND MEDIUM SIZE EXPORTING FIRMS IN SOUTH-SOUTH, NIGERIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2018)
The study investigated the relationship between innovativeness and sales performance of food and beverage exporting Small and Medium Enterprises (SMEs) firms sector in South-South, Nigeria.The study adopted descriptive survey research design, with the questionnaire as the instrument for primary data collection from a population involving 160 firms involved in exporting food and beverages. A copy of the questionnaire was administered to the sample made up of managers and owners of the firms. The questionnaire was validated by experts drawn from the marketing department of the University of Nigeria, Nsukka. The reliability test result using Cronbach Alpha produced a value of 0.844.  Both descriptive and inferential statistical tools were employed to analyze the data with SPSS (version 21.0).  The statistical result showed that, innovativeness had positive and significant relationship with sales performance. The study concluded that innovativeness  plays critical role in enhancing sales performance of food and beverage exporting SMEs in South-South, Nigeria. Therefore, this study recommended food and beverage exporting firms should be innovative as a means towards improving sales performance.